A justification for continued management of turfgrass during economic contraction. Issue 1 (12th October 2020) - Brosnan, James T.; Chandra, Ambika; Gaussoin, Roch E.; Kowalewski, Alec; Leinauer, Bernd; Rossi, Frank S.; Soldat, Douglas J.; Stier, John C.; Unruh, J. Bryan
Abstract: A novel coronavirus, termed COVID‐19, spread worldwide and become a global pandemic in 2020. Forecasts show that COVID‐19 will cause substantial economic contraction affecting almost every industry. Managed turfgrass, particularly in urban settings, has many positive societal and environmental benefits. In a contracted economy, will resources be available to manage turfgrass to achieve these benefits? In this paper, we outline the benefits of managed turfgrass on golf courses, playing fields, recreational parks, and urban landscapes to assist decision makers with resource allocation in the COVID‐19 era.